Fortalecimiento del servicio civil para mejorar la calidad del servicio público en la municipalidad distrital de Curgos, año 2016 - Carranza Campos, Leonarda Leonila (2017)
The present study was carried out in the District Municipality of Curgos, Province of Sánchez Carrión, Region La Libertad, Peru; its main objective is to determine how the Strengthening of the Civil Service in the Quality of the Public Service of the District Municipality of Curgos influences. The problematic reality has been examined and the research problem has been formulated: How does the Strengthening of the Civil Service influence the Quality of Public Service in the District Municipality of Curgos, year 2016?. In order to collect data, two populations have been taken into account, constituting in themselves the samples: twenty managers responsible for area and 15 representatives of the neighborhood meetings. The respective surveys have been applied, obtaining the results that have served as the basis for the corresponding analysis and discussion, thus demonstrating the validity of the hypothesis: "The Strengthening of the Civil Service has a positive influence on the Quality of Service Public in the District Municipality of Curgos, year 2016 ". As a final part, the conclusions and recommendations have been formulated: the main conclusion is that Civil Service Strengthening positively influences Public Service Quality, according to the Pearson correlation coefficient (0.9773) and significantly according to the t-student value (7,969), in turn quantitatively differ only in 3.19 qualification points, and qualitatively the dimensions of both variables are related by their theoretical and empirical nature. And as a main recommendation it establishes that to reinforce the Civil Service in the Municipality of Curgos the new Regime that the government has been promoting through SERVIR (according to Civil Service Law N°30057 and other complementary directives) must be Facilitate the methodology, recognition and support by the central government.